A Pragmatic Analysis of Emergent Leaders in Leaderless Group Discussion - Norman Shiddiq Prayitno; Intan Pradita (Journal of English Language Teaching and English Linguistics, 2022)
Group discussion has played significant roles in establishing students’ collaborative skills, especially leadership. This issue is interesting to discuss since the process of establishing the skills tends to happen when the students are involved in leaderless group discussion. Previous studies suggested that leaderless group discussion has been dominated by the emergence of male students as the leader so that the engagement developed. In fact, leaderless group discussion is essential to develop students’ leadership attitude. Thus, leadership attitude should not be dependent on only one gender. To extend this issue in EFL context, especially in Indonesia, this research aims to elaborate the emergence of leadership attitude by higher education students during leaderless group discussion. Two recordings of online synchronous leaderless group discussion were collected as the data. To analyze the data, we used Speech Acts of Request and Big Five Theory of leadership attitude. This research found that female students emerged as the leader and the male students acted to be the supporting group members. The female students lead the group discussion by performing feminine leadership attitudes such as extraversion, intelligence and authoritarianism. These attitudes were manifested through the speech acts of request such as conventionally indirect (query) and direct act of request (suggestory). These findings denied the stigma that only the male gender with authoritarianism is more likely to emerge during leaderless group discussion, as for females were able to emerge by relying on not just authoritarianism but also extraversion and intelligence behind that.